Rejection Collocation in the Poetry of Al-Oubairid Ibn Al-Muaazar Al-Riahi: A Structural-Genetic Study - Bitar, Lujain Mohammed Adnan (Dirasat: Human and Social Sciences, 2025)
Objectives: The study focuses on a new literary aspect in Al-Oubairid’s poetry—rejection—and its manifestation, aiming to deepen the understanding of Umayyad literature and its interaction with the socio-political realities of the era. Methods: Employing a structural-genetic approach, the research traces cognitive generators stemming from "rejection collocation" and their evolution. These generators, whether fostering authentic or flawed concepts, shape the Arab social fabric and often perpetuate inherited ideas. The study examines collocations of rejection related to separation, humiliation, animals, and women, highlighting how these notions influence traditions. Results: "Rejection collocation," deeply rooted in Arab thought, allows researchers to deconstruct entrenched ideas by analyzing their origins and evolution. This process challenges unfounded claims and dismantles illusionary constructs, drawing insights from historical and cultural heritage. Conclusion: The study underscores poetry’s role in shaping social consciousness, revealing intellectual binaries such as adherence and authority. Balancing modification and moderation exposes denial within thought structures, enriching the understanding of Arab intellectual heritage.